Human caspase-4 detects tetra-acylated LPS and cytosolic Francisella and functions differently from murine caspase-11 - Brice Lagrange (Nature Portfolio, 2018)
Lipid A from some bacteria is sensed differently by humans and mice for the activation of the inflammasomes and inflammatory responses, but the mechanisms are not clear. Here, the authors show that murine caspase-11 and human caspase-4/5 contribute to this differential response via their distinct recognition of under-acylated lipid A.